Women in the contemporary society : issues and challenges - Binarani Devi, Thokchom (New Delhi : Concept Publishing Company Pvt. Ltd., 2017)
With reference to Northeastern India.
Includes bibliographical references (pages 196-199) and index.
Keywords: Women in development -- India, Northeastern; Women -- Political activity -- India, Northeastern; Women -- India, Northeastern -- Social conditions